러시아 연해주 경남농장개발 타당성 조사 및 기본계획 수립 - 김경덕 (한국농촌경제연구원, 2009)
The purpose of this study was to take a feasibility test and set up the basic scenario for the farm development project of Kyung-Nam Province in Primorsky, Russia. One basic scenario of the farm development project in Primorsky is to set up a farm cultivating corn and soybean in 2,000 ha farm size in the primary stage. According to the feasibility test, the farm development project would be profitable. The financial internal rate of returns of a basic scenario was calculated as 14.07%, this figure would be acceptable for passing criteria of investment in developing countries. The literature suggests investment strategies on farm development in Primorsky, Russia. To alleviate the uncertainty and irreversibility problems in investment decision, strategic collaboration and join venture with existed farms is needed. Also to promote friendship with filed organizations and village people is suggested to reduce problems and difficulties owing to the less transparency in business activities.